Association between sarcoidosis and lymphoma revisited. Issue 3 (March 1996) - Karakantza, M; Matutes, E; MacLennan, K; O'Connor, N T; Srivastava, P C; Catovsky, D
Abstract : AIMS: To investigate the relation between sarcoidosis and lymphoma. METHODS: The hospital notes of five patients with sarcoidosis and a lymphoproliferative disorder were reviewed. Histological material on which the diagnoses of sarcoidosis and lymphoma were made was re-analysed. RESULTS: Four of the five patients had well documented sarcoidosis preceding the development of lymphoma by 18 months to 28 years; the fifth patient had lymphoplasmacytic lymphoma with a reactive granuloma reaction. Two patients had chronic sarcoidosis and three were treated with prednisolone. The types of lymphoma were: Hodgkin's disease (n = 1), B cell lymphoma (n = 2) (mantle cell and lymphoplasmacytic/local plasmacytoma) and large granular lymphocyte leukaemia (T cell) (n = 1). CONCLUSIONS: The association between sarcoidosis and lymphoma is confirmed, suggesting that sarcoidosis may be a predisposing factor for the development of a lymphoid malignancy due to disturbance of the immune system. All types of lymphoma may develop. The first case of T cell granular lymphocytic leukaemia in a patient with sarcoidosis has been documented.